In Vitro Modelling of Chlamydia trachomatis Infection in the Etiopathogenesis of Male Infertility and Reactive Arthritis - Filardo, Simone; Di Pietro, Marisa; Diaco, Fabiana; Sessa, Rosa (Frontiers in Cellular and Infection Microbiology, 2022)
Chlamydia trachomatis is an obligate, intracellular bacterium responsible for a range of diseases of public health importance, since C. trachomatis infection is often asymptomatic and, hence, untreated, leading to chronic complications, including prostatitis, infertility, and reactive arthritis. The ample spectrum of diseases caused by C. trachomatis infection is reflected in its ability to infect and multiply within a wide range of different cell types. Cervical epithelial cells, to date, have been the most studied cellular infection model, highlighting the peculiar features of the host-cell inflammatory and immune responses to the infection. Herein, we provide the up-to-date evidence on the interaction between C. trachomatis and human prostate epithelial, Sertoli and synovial cells.